2020
DOI: 10.1103/physrevb.101.134201
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of organic magnetoresistance based on kinetic equations for quantum spin correlations

Abstract: The correlation kinetic equation approach is developed that allows describing spin correlations in a material with hopping transport. The quantum nature of spin is taken into account. The approach is applied to the problem of the bipolaron mechanism of organic magnetoresistance (OMAR) in the limit of large Hubbard energy and small applied electric field. The spin relaxation that is important to magnetoresistance is considered to be due to hyperfine interaction with atomic nuclei. It is shown that the lineshape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It can also take place, for example, when the electrons and holes are injected into the QDs not optically, but electrically. It is known that in organic semiconductors the hyperfine and exchange interaction lead to electron and hole spin correlations even at room temperature, which can be evidenced in magnetoresistance [48][49][50] and modification of the total PL intensity [51,52] in small magnetic fields. Since optical orientation is very inefficient in organic semiconductors, the dynamic spin polarization may be a useful tool for spin initialization.…”
Section: B Numerical Resultsmentioning
confidence: 99%
“…It can also take place, for example, when the electrons and holes are injected into the QDs not optically, but electrically. It is known that in organic semiconductors the hyperfine and exchange interaction lead to electron and hole spin correlations even at room temperature, which can be evidenced in magnetoresistance [48][49][50] and modification of the total PL intensity [51,52] in small magnetic fields. Since optical orientation is very inefficient in organic semiconductors, the dynamic spin polarization may be a useful tool for spin initialization.…”
Section: B Numerical Resultsmentioning
confidence: 99%
“…The hops from site 1 to site 2 are possible only in the singlet state of the spins. Even without net current it leads to the relaxation of coherent combination of singlet and triplet states [37]. It is shown by the second term in r.h.s of Eq.…”
Section: Spin Dynamicsmentioning
confidence: 97%
“…To describe OMAR and dynamic polarization the theory of hopping transport that includes correlation of spins and occupation numbers should be used. Such a theory developed in [34][35][36][37] is applied in this paper.…”
Section: Modelmentioning
confidence: 99%
“…By contrast, in the strong magnetic field, the electron spin precession frequency equals to Larmor frequency which is the same for all hopping sites, so the spin relaxation gets suppressed [15]. Recently, some of us have shown that OMAR can be related to the nonequilibrium electron spin correlations [16,17], which appear due to the applied voltage. The relaxation of these correlations leads to OMAR.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we suggest to measure the current noise spectra in mesoscopic organic semiconductors. Although the nuclear spins are often assumed to be static [12,17,[24][25][26], their dynamics unavoidably takes place due to the interaction with the electrons. This dynamics is slow and does not change the average electric current.…”
Section: Introductionmentioning
confidence: 99%